TITLE OF MIHHICO ARTICLE 2024 THE RELATIONSHIP BETWEEN EFFECTIVE MIDWIFE COMMUNICATION AND THE LEVEL OF SATISFACTION WITH ANTENATALCARE SERVICES FORMOTHERS PREGNANT AT PRACTEC BEE NURHAYANI KEC. KAMPUNG RAKYAT REGENCY. BERTH BATU SELATAN - Christina Sirait; Yarni Kristiani Zai; Irmawaty Hutasoit; Dewi Sartika Hutabarat; Lidya Natalia Sinuhaji; Edi Subroto, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
The goal of the SDGs is a healthy and prosperous life with the achievement of improving health services towards universal health coverage, especially strengthening basic health services (Primary Health Care) (Ministry of National Development Planning/Bappenas, 2020) As many as 99 percent of maternal deaths due to pregnancy, childbirth or birth problems occur in developing countries. The AKI ratio is still considered quite high as targeted to be 70 per 100,000 live births by 2030 (WHO, 2019). The WHO estimates that more than 585,000 mothers die annually during pregnancy or childbirth. In southern Asia, women are 1 in 18 likely to die from pregnancy or childbirth during their lifetime. More than 50% of deaths in developing countries can actually be prevented with existing technology and relatively low cost of pregnancy and childbirth, with an AKI rate of 216 per 100,000 live births (WHO, 2019) (Saifudin 2018). Antenatal Care is an early prevention effort from pregnancy risk factors. Antenatal services are health services by health workers for mothers during their pregnancy, carried out in accordance with the antenatal service standards set out in the midwifery service standards. Antenatal services according to standards include anamnesis of physical examinations (general and obstetric), laboratory examinations for indications, and basic and special interventions according to (Ministry of Health of the Republic of Indonesia, 2018). Kata Kunci : Sustainable Development Goals, Primary Health Care, Antenatal Care